HUBUNGAN KEBERSIHAN GIGI DAN MULUT DENGAN KONDISI GINGIVA PADA SISWA SMP - Eka Sukanti; Eriyati Eriyati; Aflinda Yenti; Muhammad Faisal; Triana Dewi (Fakultas Kesehatan Universitas Muhammadiyah Sumatera Barat, 2024)
Poor oral and dental hygiene can cause plaque to build up on the surface of the teeth. Plaque buildup that is not cleaned will harden and disrupt the condition of the gingiva, resulting in inflammation of the gingiva. The aim of this research was to determine the relationship between dental and oral hygiene and gingival conditions in students at SMP Negeri 2 Baso, Agam Regency. This research uses analytical methods. Research subjects were taken using a saturated sampling technique. Data collection was carried out by examining the Plaque Index (IP) and Gingival Index (GI), with data analysis using the